2015
DOI: 10.1038/ncomms7553
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian adaptation of influenza A(H7N9) virus is limited by a narrow genetic bottleneck

Abstract: Human infection with avian influenza A(H7N9) virus is associated mainly with the exposure to infected poultry. The factors that allow interspecies transmission but limit human-to-human transmission are unknown. Here we show that A/Anhui/1/2013(H7N9) influenza virus infection of chickens (natural hosts) is asymptomatic and that it generates a high genetic diversity. In contrast, diversity is tightly restricted in infected ferrets, limiting further adaptation to a fully transmissible form. Airborne transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 59 publications
10
91
0
Order By: Relevance
“…While mixed V627 and E627 genotypes were transmitted among chickens, only the V627 or K627 genotype was transmitted to four ferrets where chicken-to-ferret or ferret-to-ferret transmission of HK3263 was observed. This observation is in agreement with the recent report of a narrow transmission bottleneck for the H7N9 virus among ferrets (44). However, this narrow transmission bottleneck was not observed for SCk1772, as both E627 and K627 could be detected from one of the two ferrets infected by SCk1772.…”
Section: Discussionsupporting
confidence: 83%
“…While mixed V627 and E627 genotypes were transmitted among chickens, only the V627 or K627 genotype was transmitted to four ferrets where chicken-to-ferret or ferret-to-ferret transmission of HK3263 was observed. This observation is in agreement with the recent report of a narrow transmission bottleneck for the H7N9 virus among ferrets (44). However, this narrow transmission bottleneck was not observed for SCk1772, as both E627 and K627 could be detected from one of the two ferrets infected by SCk1772.…”
Section: Discussionsupporting
confidence: 83%
“…HA activation pH values were measured by syncytium assay as described previously (48). Vero cells were infected at an MOI of 3 for 1 h. Sixteen hours postinfection (hpi), HA-expressing cells were incubated for 15 min with 5 g/ml TPCK-treated trypsin (Worthington Biochemical, NJ) and treated with pH-adjusted PBS buffers for 5 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…[73][74][75] for influenza), the ability to map symptoms back onto pathogen load will likely not work in general. Returning to influenza as our example, analyses of data from ferret infection studies showed that different influenza strains can generate similar viral loads but contrasting transmission potential [76,77]. Because the ferrets, in this study, were housed in cages with presumably little change in contact behaviour between different study groups, differences in transmission are not attributable to differences in host contact behaviour or viral load, but instead must be attributed to other features, such as qualitative differences in the virus [78] or differences in host infectiousness mediated by symptoms (e.g.…”
Section: Host Infectiousnessmentioning
confidence: 99%